Social, Economic, and Religious Behavior in The Tradition of The Labuh Saji Ceremony - Aris Munandar (FISIP UIN SGD Bandung, 2022)
One of the concrete manifestations of community behavior that respects their ancestors is the traditional Labuh Saji ceremony carried out by the fishing community of Palabuhanratu Village as an expression of gratitude to Sang Hyang Widi, who provides welfare in their lives. This study uses a descriptive qualitative method, which describes the traditional ceremony of Labuh Saji. The data obtained are in the form of observational data, interviews, and document studies. To analyze the data that will be collected, the writer will do it using data unitization, data categorization, and data interpretation. To test the validity of the data was carried out by extending participation, persistence in making observations, adequacy of references, case studies, and detailed descriptions. From the research results, it was concluded that the people of Palabuhanratu Village are still firm in upholding the traditions of their ancestors and preserving local cultural wisdom, such as carrying out the traditional Labuh saji ceremony. As for the concept of the ceremony, first, determine the place of implementation, then prepare the necessary equipment. The implementation process begins with various remarks from the committee and government officials. The community makes social contact, resulting in social interaction, and this ceremony is a medium of friendship between the local community. In the economy, the ceremony is a driving factor for community welfare, then in religious behavior, Labuh saji is a form of expression and gratitude for the abundance of sustenance received by the fishing community of Palabuhanratu.